Clinical parameters of hypervirulent Klebsiella pneumoniae disease and ivermectin treatment in New Zealand sea lion (Phocarctos hookeri) pups. - Sarah A Michael; David T S Hayman; Rachael Gray; Wendi D Roe (PLoS ONE)
Hypervirulent Klebsiella pneumoniae infection causes significant mortality of endangered New Zealand sea lion pups at Enderby Island, Auckland Islands. Gross necropsy and histopathology findings are well reported, but little is known about the clinical course of disease in affected pups. To determine factors feasible as clinical screening tools for hypervirulent K. pneumoniae in live pups, 150 pups over two field seasons (2016-18) were recruited shortly after birth for a prospective cohort study. A randomised controlled clinical treatment trial with the anthelmintic ivermectin was conducted concurrently and risk factor data and biological samples were collected approximately fortnightly. Treatment with ivermectin has been demonstrated to reduce the risk of hypervirulent K. pneumoniae mortality in pups, so effects on clinical parameters between the treated and control cohorts were also investigated. A broader sample of pups were monitored for clinical signs to investigate the course of disease in affected pups. Clinical signs, haematology and oral and rectal swabs to detect gastrointestinal carriage of hypervirulent K. pneumoniae were not useful for detection of disease prior to death. Of those pups that died due to hypervirulent K. pneumoniae, only 26.1% (18/69) had any clinical signs prior, likely a reflection of the peracute course of disease. On comparison of haematological parameters between ivermectin-treated and control pups, significantly lower total plasma protein and higher eosinophil counts were seen in control versus treated pups, however standard length as a surrogate for age was a more important influence on parameters overall than ivermectin treatment. This study also highlighted a cohort of pups with severe clinical signs suggestive of hypervirulent K. pneumoniae infection were lost to follow up at the end of the monitored season, which could be contributing to cryptic juvenile mortality.